EFFECTIVE RADIATION DOSE OF 18F-FDG PET/CT: HOW MUCH DOES DIAGNOSTIC CT CONTRIBUTE?. Issue 2 (31st May 2019) - Li, Yuhao; Jiang, Lisha; Wang, Haitao; Cai, Huawei; Xiang, Yongzhao; Li, Lin
Abstract: The aim was to estimate the effective doses associated with different types of scanning protocols and how much the diagnostic computed tomography (DCT) scan contributed to the total dose of the dual-modality positron emission tomography/computed tomography (PET/CT) examinations. The results showed that an average radiation dose of 8.19 ± 0.83 mSv and 13.44 ± 5.14 mSv for the PET and CT components, respectively, resulting in a total dose of 21.64 ± 5.20 mSv. Approximately 92.7% (980 of 1057) of the patients underwent additional DCT protocols. The DCT protocols contributed 42% of the overall effective radiation doses, which was larger than the percentage contributed by the PET component (38%) and LCT protocols (20%). Reducing the diagnostic area of the DCT scans that patients undergo and decreasing the use of chest-abdomen-pelvis (CAP), abdomen-pelvis (AP) and chest DCT protocols, especially the CAP protocol, will be helpful in decreasing the effective radiation doses of PET/CT scan.